ANALISI PERENCANAAN BAHAN BAKU UNTUK MEMINIMALISASI PENGGUNAAN RUANG PENYIMPANAN DI RAW MATERIAL PT. WIJAYA KARYA BETON Tbk. PPB MAJALENGKA - Aradea Muhammad Nurul Azhar, Reza; Whydiantoro (Universitas Majalengka, 2021)
Building and maintaining infrastructure, can be said to be the same as building the future and civilization of a country. Referring to the 2018 World Bank Group, in 2018 Indonesia's infrastructure competitiveness was ranked 52nd, this achievement can be said to be good when compared to 2010-2013 which was in the 70s. Then based on a study conducted by Tusk Advisory in 2018, the long-term benefits generated by infrastructure development, especially the development of PSN (National Strategic Projects), are predicted to have an impact on an increase in GDP (Gross Domestic Product) of 7.2% in 2023 and 9, 3% in 2030. In realizing an effective and efficient production process and producing products in accordance with predetermined standards, a company must implement a policy, especially in terms of planning and controlling raw material inventory and production activities. The inventory management is aims to reduce a material fluctuation risk and production cost. The availability of raw materials is crucial in determining whether a production activity can run well or not. Delays or unavailability of raw materials can disrupt the company's production process. In order to avoid and minimize this, the company is expected to form a proactive management that is not only taking the initiative, but is responsible and brings good change, so that it can achieve the company's goals.